2000
DOI: 10.1046/j.1464-410x.2000.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Placebo‐associated remissions in a multicentre, randomized, double‐blind trial of interferon γ‐1b for the treatment of metastatic renal cell carcinoma

Abstract: Objective To determine the validity of using an historical maximum spontaneous regression rate (reportedly 0±1.1% in those with lung metastases after nephrectomy) in clinical trials of treatments for patients with metastatic renal cell carcinoma (RCC), as the eligibility criteria for most studies will select patients with better performance status (and thus excluding those who are unlikely to respond) and more modern staging methods would potentially reduce the number of false-positives. Patients and methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…Approval decisions have often been bolstered by quality-of-life outcomes, a type of evidence that is not generally available for phase I oncology studies. 16 Further complicating the reliance on phase I meta-analyses, open-label phase I studies cannot exclude natural regression [17][18][19][20] or radiography error. One systematic review of cancer trials found that patients in placebo arms showed a 2.4% response rate.…”
Section: Evidencementioning
confidence: 99%
“…Approval decisions have often been bolstered by quality-of-life outcomes, a type of evidence that is not generally available for phase I oncology studies. 16 Further complicating the reliance on phase I meta-analyses, open-label phase I studies cannot exclude natural regression [17][18][19][20] or radiography error. One systematic review of cancer trials found that patients in placebo arms showed a 2.4% response rate.…”
Section: Evidencementioning
confidence: 99%
“…Evidence that clear-cell RCC is an immunogenic tumour includes observed spontaneous tumour regression in 1 -4% of patients (Elhilali et al, 2000), the presence of lymphocytic infiltrates in tumour, and responsiveness of RCC to cytokine therapy. A number of studies have been reported demonstrating the ability of interferon alpha and interleukin-2 (IL-2) to engender a tumour response (Fyfe et al, 1995;Pyrhonen et al, 1999;MRCRC Collaborators, 1999;Yang et al, 2003b;McDermott et al, 2005).…”
mentioning
confidence: 99%
“…Whereas several adult solid cancers have been documented to occasionally regress in the absence of therapy, melanoma and renal cell carcinoma (renal cell carcinoma) compose the significant majority of such observations (12). Metastatic renal cell carcinoma may regress partially or completely in up to 6% to 7% of cases and durations may be prolonged (13,14). Such responses to placebo have led to the suggestion that a minimum response rate of 18% be required of an agent in phase II studies before proceeding to phase III studies (14).…”
mentioning
confidence: 99%
“…Metastatic renal cell carcinoma may regress partially or completely in up to 6% to 7% of cases and durations may be prolonged (13,14). Such responses to placebo have led to the suggestion that a minimum response rate of 18% be required of an agent in phase II studies before proceeding to phase III studies (14). Pathologic assessment of melanoma specimens suggests some degree of remission in 10% to 36% of cases (15).…”
mentioning
confidence: 99%